Challenges and Opportunities in Education Equity through the 13-Year Compulsory Education Program in Indonesia - Judijanto, Loso (The Eastasouth Journal of Learning and Educations, 2025)
The 13-Year Compulsory Education Program in Indonesia aims to equalize educational opportunities and address longstanding disparities in access and quality. This study employs a qualitative approach, gathering insights from six key informants, including policymakers, educators, community leaders, and NGO representatives, to explore the program's challenges and opportunities. Key challenges identified include infrastructure gaps, teacher shortages, socio-economic barriers, and logistical difficulties in archipelagic areas. However, opportunities such as technology integration, public-private partnerships, community engagement, and teacher training offer promising solutions for achieving educational equity. The findings underscore the importance of multi-faceted strategies, collaborative efforts, and targeted policies to overcome barriers and maximize the program's potential.